Thermal Optimization of Aluminium Fishing Sinker Mold Using Cooling Channel Design - Yahya Hafiizh Arifin; Akhri Ramadhan Putra; fardin hasibuan; Muhammad Irsyam (Universitas Riau Kepulauan, 2026)
Thermal performance of mold plays a critical role in determining the quality and productivity of aluminium casting products, including fishing sinkers. Improper temperature distribution within the mold can lead to casting defects, uneven solidification, and extended cooling time. This study focuses on the thermal optimization of an aluminium fishing sinker mold through the design and improvement of cooling channel configurations. Numerical simulations based on heat transfer analysis are conducted to evaluate temperature distribution, cooling efficiency, and solidification behavior within the mold. Several cooling channel designs are analyzed and compared to identify the most effective configuration for achieving uniform temperature distribution and enhanced heat dissipation. The results show that optimized cooling channel design significantly reduces temperature gradients, shortens cooling time, and improves overall casting quality. This study demonstrates that thermal optimization through proper cooling channel design is an effective approach to enhancing the performance and reliability of aluminium fishing sinker molds.